Post Transplantation Bilirubin Nanoparticles Ameliorate Murine Graft Versus Host Disease via a Reduction of Systemic and Local Inflammation - Pareek, Sumedha; Flegle, Alexandra S.; Boagni, Drew; Kim, Jin Yong; Yoo, Dohyun; Trujillo-Ocampo, Abel; Lee, Sung-Eun; Zhang, Mao; Jon, Sangyong; Im, Jin S. (Frontiers in Immunology, 2022)
Allogeneic stem cell transplantation is a curative immunotherapy where recipients receive myeloablative chemotherapy and/or radiotherapy, followed by donor stem cell transplantation. Graft versus host disease (GVHD) is a major complication caused by dysregulated donor immune system, thus a novel strategy to modulate donor immunity is needed to mitigate GVHD. Tissue damages by conditioning regimen is thought to initiate the inflammatory milieu that recruits various donor immune cells for cross-priming of donor T cells against alloantigen and eventually promote strong Th1 cytokine storm escalating further tissue damages. Bilirubin nanoparticles (BRNP) are water-soluble pegylated bilirubin with potent anti-inflammatory properties through its ability to scavenge reactive oxygen species generated at the site of inflammation. Here, we evaluated whether BRNP treatment post-transplantation can reduce initial inflammation and subsequently prevent GVHD in a major mismatched murine GVHD model. Sub-lethally irradiated BALB/c mice received bone marrow and splenocytes isolated from C57BL/6, with or without BRNP (10mg/kg) daily on days 0 through 4 post-transplantation and clinical GVHD and survival was monitored for 90 days. First, BRNP treatment significantly improved clinical GVHD score compared to untreated mice (3.4 vs 0.3, p=0.0003), and this translated into better overall survival (HR 0.0638, p=0.0003). Further, BRNPs showed a preferential accumulation in GVHD target organs leading to a reduced systemic and local inflammation evidenced by lower pathologic GVHD severity as well as circulating inflammatory cytokines such as IFN-γ. Lastly, BRNP treatment post-transplantation facilitated the reconstitution of CD4+ iNK T cells and reduced expansion of proinflammatory CD8α+ iNK T cells and neutrophils especially in GVHD organs. Lastly, BRNP treatment decreased ICOS+ or CTLA-4+ T cells but not PD-1+ T cells suggesting a decreased level of T cell activation but maintaining T cell tolerance. In conclusion, we demonstrated that BRNP treatment post-transplantation ameliorates murine GVHD via diminishing the initial tissue damages and subsequent inflammatory responses from immune subsets.